Release resin composition, release film, and adhesive tape
Patent Information
- Application Number
- JP2025057564
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0014】 本発明の剥離用フィルム及び剥離性樹脂組成物はシリコーンを含まず、粘着テープに対して、従来のポリエチレン系樹脂組成物からなる離型剤に比べてより改善された初期の易剥離性を有すると共に、湿熱エージング後においても良好な易剥離性を有し、剥離性樹脂組成物としての要求特性を十分満足するものである。
Smart Images

Figure 2026165269000003 
Figure 2026165269000004 
Figure 2026165269000005
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a peelable resin composition for forming a release layer provided on the back surface of an adhesive tape or the like, and a release film and an adhesive tape using the same. In the present invention, the term "film" used for the "release film" is used as a concept that also includes sheets. BACKGROUND ART
[0002] Adhesive tapes are currently known for various uses such as protection of daily necessities, building materials, and electronic components. The adhesive tape structure is a laminate (tape, sheet, film) composed of an adhesive layer made of an adhesive formed on one surface of a base material, and a release layer (also referred to as a release agent layer) provided on the back surface of the base material. Several combinations of adhesive layers and release layers are used depending on the required adhesive strength, easy peel strength, and the price range matching the intended use. For example, rubber-based, acrylic-based, and silicone-based adhesives are known as the adhesives constituting the adhesive layer. In addition, the release film has a release layer on at least one side of a base material, and is widely used to protect adhesive surfaces or bonding surfaces. The peelable resin composition constituting the release layer (hereinafter also referred to as "release agent") is roughly classified into silicone-based release agents and non-silicone-based release agents.
[0003] Silicone-based release agents have excellent easy peel properties, but in the fields of electronic devices and electrical devices, there is a problem that trace amounts of generated siloxane-based gas cause corrosion, contact failures, and the like. In recent years, there has been a growing demand for non-silicone peelable resin compositions (release agents), particularly olefin-based release agents, instead of silicone-based ones, as environmentally friendly materials.
[0004] Examples of non-silicone release agents include release agents with reduced surface energy by halogen compounds such as fluorides, and polyvinyl carbamate which is a polymer containing long-chain alkyl groups (PVA and C 18 H 37A release agent consisting of a reaction product with NCO, polyethyleneimine and C 18 H 37 Release agents consisting of reaction products with NCO, release agents consisting of copolymers mainly composed of perfluoroalkyl vinyl, and release agents consisting of polyethylene resin compositions have been proposed.
[0005] Non-silicone release agents have the advantage of not generating siloxane-based gases. However, generally, non-silicone release agents require a greater release force than silicone-based release agents. Furthermore, non-silicone release agents have specific problems depending on the material system used, as described below.
[0006] For example, mold release agents that reduce surface energy using halogen compounds such as fluorides do not align with the current trend of de-halogenation to reduce the environmental burden in waste disposal. Furthermore, mold release agents composed of copolymers primarily made of perfluoroalkyl vinyl have excellent peelability, but their applications are severely limited because they are generally insoluble in organic solvents and only dissolve in special, expensive solvents such as FR thinner.
[0007] Furthermore, release agents made from polyethylene resin compositions include release agents mainly composed of low-density polyethylene resin (see, for example, Patent Document 1) and release agents mainly composed of high-density polyethylene resin (see, for example, Patent Documents 2 and 3). Release agents mainly composed of low-density polyethylene resin require a large peeling force, and when used as a protective film for a pressure-sensitive adhesive layer, they have problems such as a portion of the adhesive layer migrating to the surface of the release layer during peeling, or causing a type of peeling called stick-slip, where the surface shape of the adhesive layer after peeling becomes pulsed. Release agents mainly composed of high-density polyethylene resin have problems such as poor adhesion to the substrate and a large peeling force when a polar polymer is used as the substrate.
[0008] On the other hand, adhesive tapes are sometimes exposed to high-temperature and high-humidity environments. When used in such environments, migration of adhesive components and deterioration of the release agent usually occur, leading to severe peeling and making them difficult to remove. Therefore, especially when exposed to high-temperature and high-humidity environments, there is a need for a release sheet that minimizes changes in peel strength, preferably maintaining its initial easy peelability. However, a mold release agent made from a polyethylene-based resin composition that maintains its easy-release properties even after being heated has not yet been realized.
[0009] Furthermore, while some non-silicone mold release agents have been commercialized, mold release agents made from polyethylene resin compositions are also required to have initial release properties equivalent to or better than these non-silicone mold release agents. [Prior art documents] [Patent Documents]
[0010] [Patent Document 1] Special Publication No. 11-508958 [Patent Document 2] Japanese Patent Publication No. 2000-239624 [Patent Document 3] Japanese Patent Publication No. 2000-119411 [Overview of the project] [Problems that the invention aims to solve]
[0011] In view of the above problems, the object of the present invention is to provide a release film and a release resin composition that do not contain silicone, have excellent initial release properties for various adhesives, and further have good release properties even after moist heat aging. [Means for solving the problem]
[0012] As a result of diligent research to solve the above problems, the present inventors have found that a laminate (release film) formed by forming a release layer on a substrate layer using a polyethylene resin composition comprising a release resin composition containing linear low-density polyethylene polymerized using a multi-site catalyst having specific physical properties, and further comprising an ethylene-propylene copolymer having the following new range of physical properties (c-1) to (c-5), namely, an ethylene-propylene copolymer containing predetermined amounts of ethylene as the main component and propylene as the secondary component, with density and MFR within a certain range, a large amount of double bonds in the copolymer, and a large number of branches, exhibits improved initial release properties compared to conventional release agents made from polyethylene-based resin compositions, and also maintains good release properties even after moist heat aging, thus completing the present invention.
[0013] In other words, the present invention has the following configuration. [1] A releaseable resin composition comprising an ethylene-propylene copolymer (C) having all of the following properties (c-1) to (c-5), and a polyethylene resin composition (F) containing linear low-density polyethylene (E) polymerized using a multi-site catalyst having the following properties (e-1) to (e-2). (c-1) Contains 80-98 mol% of ethylene-derived structural units as the main component, 2-20 mol% of propylene-derived structural units as an essential minor component, and may also contain 7 mol% or less of structural units derived from a third α-olefin other than ethylene and propylene as an optional minor component. (However, if the material contains constituent units derived from the third α-olefin, the sum of constituent units derived from ethylene, propylene, and the third α-olefin shall not exceed 100 mol%.) (c-2) MFR (190℃, 21.18N load) is 1-100g / 10min (c-3) Density of 0.88~0.94 g / cm³ 3 (c-4) The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.20 (particles / total 1000C) or more. (However, the number of vinyl and vinylidene atoms is the number per 1000 carbon atoms in the main chain and side chains, as measured by NMR.) (c-5) The relationship between the number of branches (Y) and the density (X) of comonomers in an ethylene-propylene copolymer is given by the following equation (1). Equation (1): (Y) ≥ -566 × (X) + 540 (However, Y is the number of carbon atoms per 1000 total carbon atoms in the main chain and side chains as measured by NMR.) (e-1) MFR (190℃, 21.18N load) is 0.1~30g / 10min (e-2) Density of 0.906~0.930 g / cm³ 3 [2] The releaseable resin composition according to [1], characterized in that the polyethylene resin composition (F) further contains high-pressure radical polymerization low-density polyethylene (D) having the following properties (d-1) to (d-2). (d-1) MFR (190℃, 21.18N load) is 0.1~20g / 10min (d-2) Density of 0.915~0.930 g / cm³ 3 [3] The releaseable resin composition according to [2], characterized in that the polyethylene resin composition (F) contains 95 to 10% by weight of ethylene-propylene copolymer (C) and linear low-density polyethylene (E) and 5 to 90% by weight of low-density polyethylene (D) produced by high-pressure radical polymerization. [4] The releaseable resin composition according to any one of [1] to [3], characterized in that the polyethylene resin composition (F) further satisfies the following properties (f-1) to (f-2). (f-1) MFR is 1-100g / 10min (f-2) Density of 0.91-0.93 g / cm³ 3 [5] The release resin composition according to any one of [1] to [4], characterized in that the ethylene-propylene copolymer (C) further satisfies the following physical properties (c-4'). (c-4') The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.35 (particles / total 1000C) or more. (However, the number of vinyl and vinylidene atoms is the number per 1000 carbon atoms in the main chain and side chains, as measured by NMR.) [6] The release resin composition according to any one of [1] to [5], characterized in that the ethylene-propylene copolymer (C) further satisfies the following physical properties (c-5'). (c-5') The number of branches (Y) and density (X) due to comonomers in the ethylene-propylene copolymer satisfy the relationship shown in equation (2) below. Equation (2): (Y) ≥ -1360 × (X) + 1270 (However, Y is the number of carbon atoms per 1000 total carbon atoms in the main chain and side chains as measured by NMR.) [7] The release resin composition according to any one of [1] to [6], characterized in that the ethylene-propylene copolymer (C) substantially does not contain any constituent units derived from a third α-olefin other than ethylene and propylene. [8] A release film having at least two layers, a resin layer (A) and a base layer (B), wherein the resin layer (A) contains a polyethylene resin composition (F) as described in any one of [1] to [7], and is formed by laminating it directly on the base layer (B) or on top of another resin layer laminated on the base layer, and at least one resin layer (A) is the outermost layer. [9] The release film according to [8], characterized in that the resin layer (A) is formed on the base material layer (B) by an extrusion coating method.
[10] An adhesive tape having at least three layers: a resin layer (A), a base layer (B), and an adhesive layer (G), wherein the resin layer (A) contains a polyethylene resin composition (F) as described in any one of [1] to [7], the resin layer (A) is formed either directly on the base layer (B) on the side opposite to the side on which the adhesive layer (G) is provided, or by laminating it on other resin layers laminated on the base layer, and at least one resin layer (A) is the outermost layer.
[11] The adhesive tape according to
[10] , characterized in that the adhesive layer is made of an acrylic adhesive. [Effects of the Invention]
[0014] The release film and release resin composition of the present invention do not contain silicone, and have improved initial release properties compared to conventional release agents made of polyethylene-based resin compositions when applied to adhesive tapes. They also maintain good release properties even after moist heat aging, and fully satisfy the required characteristics of a release resin composition. [Brief explanation of the drawing]
[0015] [Figure 1] Figure 1 is a schematic diagram showing a cross-section of an example of the release film of the present invention. [Figure 2] Figure 2 is a schematic diagram showing a cross-section of another example of the release film of the present invention. [Figure 3] Figure 3 is a graph showing the relationship between the time spent in the moist heat aging test and the peel strength for Examples 1 and 2, Comparative Example 1, and Reference Example 1. [Explanation of Symbols]
[0016] 1 Base material layer (B) 2. A different resin layer from resin layer (A) 3 Resin layer (A) [Modes for carrying out the invention]
[0017] 1. Release resin composition One embodiment of the present invention is a release resin composition comprising an ethylene-propylene copolymer (C) having all of the properties described later in (c-1) to (c-5) and a polyethylene resin composition (F) containing linear low-density polyethylene (E) polymerized using a multi-site catalyst having the properties described in (e-1) to (e-2) (hereinafter also referred to as "the release resin composition of the present invention"). The components used in this invention will be described in detail below.
[0018] (1-1) Polyethylene resin composition (F) The polyethylene resin composition (F) (hereinafter also simply referred to as the resin composition) used in the releaseable resin composition of the present invention is characterized by containing linear low-density polyethylene (E) polymerized using a multi-site catalyst and containing an ethylene-propylene copolymer (C). Furthermore, the polyethylene resin composition (F) preferably further contains high-pressure radical polymerization low-density polyethylene (D), and more preferably contains 95-10% by weight of ethylene-propylene copolymer (C) and linear low-density polyethylene (E) and 5-90% by weight of high-pressure radical polymerization low-density polyethylene (D).
[0019] (1) Ethylene-propylene copolymer (C) The ethylene-propylene copolymer (C) used in the present invention has the following properties (c-1) to (c-5). (c-1) Contains 80-98 mol% of constituent units derived from ethylene as the main component, 2-20 mol% of constituent units derived from propylene as an essential minor component, and may also contain 7 mol% or less of constituent units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, if the material contains constituent units derived from the third α-olefin mentioned above, the total amount of constituent units derived from ethylene, propylene, and the third α-olefin shall not exceed 100 mol%.) (c-2) MFR (190℃, 21.18N load) is 1-100g / 10min (c-3) Density is 0.88 to 0.94 g / cm 3 (c-4) The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.20 (units / total 1000C) or more (Here, the number of vinyl and vinylidene is the number per total of 1000 carbon atoms in the main chain and side chains measured by NMR.) (c-5) The branch number (Y) derived from the comonomer in the ethylene-propylene copolymer and the density (X) satisfy the relationship of the following formula (1). Formula (1): (Y) ≧ -566 × (X) + 540 (Here, Y is the number per total of 1000 carbon atoms in the main chain and side chains measured by NMR.)
[0020] Incidentally, as copolymers containing ethylene and propylene as constituent components, so-called ethylene-propylene rubber (EPM), which contains a propylene component in an amount of more than 20 mol% and has a density of 0.870 g / cm 3 The following rubbery polymers obtained by a solution polymerization method are used in the field of elastomers, but the ethylene-propylene copolymer (C) used in the present invention is a polymer that differs from these ethylene-propylene rubbers in the density range, the amounts of ethylene and propylene contained, and also completely different in physical properties and the like. Further, among propylene polymers, propylene-ethylene copolymers containing a slight amount of an ethylene component in the production process are also known, but these are also greatly different from the ethylene-propylene copolymer (C) used in the present invention in terms of propylene content and the like, and are polymers having completely different physical properties and the like. In addition, so-called ordinary ethylene-α-olefin copolymers having a linear molecular structure (for example, LLDPE) have been developed mainly for film applications, so it is usual to use an α-olefin of C4 or more such as C4 and C6 as the main comonomer component to obtain a high-strength copolymer, and a copolymer composed of ethylene and propylene using a C3 comonomer that gives low strength as the main subcomponent, with a density of 0.88 g / cm 3 The above copolymers have received little attention so far, and at least have not been commercially available from the present applicant. In this study, we have newly fabricated an ethylene-propylene copolymer using a C3 comonomer in the aforementioned density range as the main minor component, and after various investigations, we have found that the effects of the present invention can be obtained in a release resin composition comprising an ethylene-propylene copolymer having new physical properties in the ranges of (c-1) to (c-5), and a polyethylene resin composition (F) containing at least linear polyethylene (E).
[0021] (i) Properties of ethylene-propylene copolymer (C) (c-1) Monomer composition The ethylene-propylene copolymer (C) used in the present invention is an ethylene-propylene copolymer characterized by containing 80 to 98 mol% of constituent units derived from ethylene as the main component and 2 to 20 mol% of constituent units derived from propylene as a minor component. A specific example is a copolymer polymerized by catalytic polymerization, which is a copolymer polymerized in a substantially linear and random manner. A specific example is a random copolymer of ethylene and propylene. Preferably, the constituent units derived from ethylene are 82 to 97 mol%, the constituent units derived from propylene are 3 to 18 mol%, and more preferably, the constituent units derived from ethylene are 85 to 95 mol%, and the constituent units derived from propylene are 5 to 15 mol%. Here, the monomer amounts such as the ethylene content are values measured and calculated by 13C-NMR under the conditions described in the examples described later.
[0022] Furthermore, a composition that does not contain any other α-olefins, particularly α-olefins having 4 to 20 carbon atoms, and other monomer components is preferred, but such a composition may be included in substantially trace amounts. In this specification, α-olefins other than ethylene and propylene are referred to as third α-olefins. The ethylene-propylene copolymer (C) used in the present invention may contain, for example, 7 mol% or less, preferably 7 mol% or less, more preferably 5 mol% or less, even more preferably 1 mol% or less, and most preferably 0.5 mol% or less of constituent units derived from third α-olefins other than ethylene and propylene as minor components. Furthermore, in a more preferred embodiment of the present invention, the ethylene-propylene copolymer (C) substantially contains no constituent units derived from a third α-olefin other than ethylene and propylene. Here, if the ethylene-propylene copolymer (C) contains structural units derived from a third α-olefin, the total of the structural units derived from ethylene, propylene, and the structural units derived from the third α-olefin shall not exceed 100 mol%. In this case, it is preferable that the content of structural units derived from propylene is higher than the content of structural units derived from the third α-olefin. Furthermore, if the ethylene-propylene copolymer (C) of the present invention contains structural units derived from a third α-olefin, one or more third α-olefins can be used. Furthermore, the ethylene-propylene copolymer (C) may be one type or a combination of two or more types, as long as it satisfies (c-1) to (c-5).
[0023] When propylene is used as an essential comonomer as a minor component, and especially when a high-pressure ionic polymerization method using a metallocene catalyst, as described later, is employed, it is possible to obtain ethylene-α-olefin copolymers with a particularly high total number of vinyl and vinylidene molecules. This effect is difficult to obtain when α-olefins such as 1-butene, 1-hexene, and 1-octene are used as the main comonomer components during polymerization.
[0024] (c-2) MFR The ethylene-propylene copolymer (C) used in the present invention has a melt flow rate (MFR: 190°C, 21.18N load) of 1 to 100 g / 10 min, preferably 1 to 80 g / 10 min, and more preferably greater than 5 g / 10 min and 60 g / 10 min or less. An MFR of less than 1 g / 10 min is undesirable because it results in poor ductility during lamination molding and increases the motor load in the extruder. On the other hand, an MFR exceeding 100 g / 10 min is undesirable because it makes the state of the molten film unstable during molding. To adjust the MFR of a polymer, methods such as appropriately adjusting the polymerization temperature and comonomer amount are employed. The MFR of ethylene-propylene copolymers is measured in accordance with JIS-K6922-2:1997 Annex (190°C, 21.18N load).
[0025] (c-3) Density The ethylene-propylene copolymer (C) used in this invention has a density of 0.88 to 0.94 g / cm³. 3 The concentration is preferably 0.88 to 0.93 g / cm³. 3 More preferably 0.88~0.92 g / cm³ 3 Its density is 0.88 g / cm³. 3 If the density is less than 0.94 g / cm³, it will result in poor blocking and is therefore undesirable. On the other hand, a density of 0.94 g / cm³ is undesirable. 3 If it exceeds this value, the peeling characteristics will be poor, which is undesirable. To adjust the density of the polymer, methods such as appropriately adjusting the comonomer content, polymerization temperature, and catalyst amount are employed. The density of ethylene-propylene copolymer is measured in accordance with JIS-K6922-2:1997 Annex (for low-density polyethylene) (measurement temperature 23°C).
[0026] (c-4) Total number of vinyl and vinylidene In copolymers formed by copolymerizing ethylene with one or more α-olefins, even without the active addition of diene monomers, various double bonds (vinyl, vinylidene, cis-vinylene, trans-vinylene, trisubstituted olefins) may be formed due to differences in the manufacturing process mechanism, and their quantity and type vary.
[0027] The ethylene-propylene copolymer (C) used in the present invention has a total number of vinyl and vinylidene double bonds per 1000 carbon atoms in the main chain and side chains, as measured by NMR, of 0.20 (bonds / total 1000C) or more, preferably 0.30 to 5.0 (bonds / total 1000C), more preferably 0.35 to 4.5 (bonds / total 1000C), and even more preferably 0.50 to 4.0 (bonds / total 1000C). When the total number of vinyl and vinylidene atoms is within the above range, the resin composition exhibits excellent release properties. If it is less than 0.20 atoms, the release properties will not be sufficient. The total number of vinyl and vinylidene atoms can be controlled within the above range by appropriately adjusting the selection of a suitable metallocene catalyst, polymerization temperature, comonomer species, and comonomer amount. The number of these double bonds is the number per 1000 carbon atoms in the main chain and side chain combined, and is a value calculated using the integrated intensity of characteristic peaks in the 1H-NMR spectrum, measured and calculated under the conditions described in the examples below.
[0028] Furthermore, the ethylene-propylene copolymer (C) used in the present invention preferably satisfies the following physical properties (c-4'). (c-4') The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.35 (particles / total 1000C) or more. (However, the number of vinyl and vinylidene atoms is the number per 1000 carbon atoms in the main chain and side chains, as measured by NMR.)
[0029] Furthermore, in the present invention, it is preferable that the number of vinyl atoms in the ethylene-propylene copolymer (C) is in the range of 0.1 (atoms / total 1000C) or more. Furthermore, in the present invention, it is preferable that the number of vinylidene molecules in the ethylene-propylene copolymer (C) is in the range of 0.05 (molecules / total 1000C) or more.
[0030] (c-5) Relationship between the number of branching (Y) and density (X) due to comonomers The ethylene-propylene copolymer (C) used in the present invention satisfies the following formula (1) in terms of the number of branches (Y) and density (X) due to the comonomer. Equation (1): (Y) ≥ -566 × (X) + 540
[0031] Furthermore, the ethylene-propylene copolymer (C) used in the present invention preferably satisfies the following physical properties (c-5'). (c-5') The number of branches (Y) and density (X) due to comonomers in the ethylene-propylene copolymer satisfy the relationship shown in equation (2) below. Equation (2): (Y) ≥ -1360 × (X) + 1270
[0032] When the density and branching number satisfy the relationship in equation (1) or (2) above, a sufficient number of branches due to the comonomers is ensured, resulting in a resin composition with excellent peeling properties. Here, the branching number due to the comonomer (Y) is the number of branches per 1000 carbon atoms in the total of the main chain and side chains of the ethylene-propylene copolymer (C), as measured by NMR (copies / total 1000C). Furthermore, density (X) is the density of the ethylene-propylene copolymer (C), and is measured as described above.
[0033] The number of comonomer branches (Y) indicates the amount of tertiary carbon contained in the polymer, and is the number per 1000 carbon atoms in the main chain and side chains combined, as measured by NMR. For example, it can be calculated from the 13C-NMR spectrum, referring to EW Hansen, R. Blom, and OM Bade, Polymer, Vol. 36, p. 4295 (1997). The relationship between density and branching can be adjusted by the type and ratio of comonomers copolymerized, polymerization conditions such as polymerization temperature, and other factors.
[0034] (ii) Polymerization catalyst and polymerization method for ethylene-propylene copolymer (C) The catalyst used in the production of the ethylene-propylene copolymer (C) used in the present invention is not particularly limited, but a metallocene catalyst is more preferred. While not particularly limited, metallocene catalysts include catalysts in which a metallocene compound, such as a zirconium compound to which a group having a cyclopentadienyl skeleton is coordinated, and a co-catalyst are used as catalytic components. In particular, it is preferable to use a metallocene compound, such as a zirconium compound to which a group having a cyclopentadienyl skeleton is coordinated. As for the manufacturing method, since polymerization at a high temperature of 150 to 330°C is desirable to obtain the ethylene-propylene copolymer (C) with adjusted double bonds according to the present invention, it is preferable to use high-pressure ionic polymerization ("Polyethylene Technology Handbook," Chapter 4, edited by Kazuo Matsuura and Naotaka Mikami, 2001).
[0035] (2) Linear low-density polyethylene (E) polymerized using a multi-site catalyst The linear low-density polyethylene (LLDPE) polymerized using the multi-site catalyst used in the present invention (hereinafter also referred to as linear low-density polyethylene (E)) is a linear polyethylene (LLDPE) having the following characteristics (e-1) to (e-2). (e-1) MFR (190℃, 21.18N load) is 0.1~30g / 10min (e-2) Density of 0.906~0.930 g / cm³ 3
[0036] In the release resin composition of the present invention, it is important that it contains linear low-density polyethylene (E) polymerized using the multi-site catalyst specified above. The release resin composition of the present invention can greatly improve initial release properties and heat resistance by containing a combination of a specific linear low-density polyethylene (E) and the ethylene-propylene copolymer (C) described in the previous section. While not intended to be constrained by theory, it is believed that the low-molecular-weight, high-comonomer components contained in linear low-density polyethylene (E) promote the surface coordination of the ethylene-propylene wax component of the ethylene-propylene copolymer (C), thereby enabling good peelability. Here, since the low-molecular-weight components of linear low-density polyethylene (E) also exhibit peelability, it is possible to provide a peelable resin composition with good peelability even without containing ethylene-propylene copolymer (C). However, when combined with the effect of adding ethylene-propylene wax by including ethylene-propylene copolymer (C), even better peelability can be achieved.
[0037] The linear low-density polyethylene (E) is a type of linear low-density polyethylene consisting of a composition other than ethylene-propylene copolymer (C), and is a polyethylene copolymer obtained by catalytic polymerization of ethylene and constituent units derived from α-olefins (comonomers) having 3 to 20 carbon atoms, and is substantially polymerized randomly in a linear shape. The catalyst is particularly preferably the Ziegler-Natta catalyst. There are no particular limitations on the α-olefin, and propylene, 1-butene, 4-methylpentene-1, 1-hexene, 1-octene, 1-decene, etc. are used. Preferably, propylene or 1-butene is preferred. Furthermore, two or more of these α-olefins may be used.
[0038] (i) Properties of linear low-density polyethylene (E) (e-1)MFR The melt flow rate (MFR: 190°C, 21.18N load) of the linear low-density polyethylene (E) used in the present invention is 0.1 to 30 g / 10 min, preferably 0.5 to 25 g / 10 min, and more preferably 1 to 20 g / 10 min. If the MFR is less than 0.1 g / 10 min, the ductility is insufficient, and film breakage occurs during high-speed molding. On the other hand, if the MFR exceeds 30 g / 10 min, the molten film becomes unstable. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Annex (190°C, 21.18N load).
[0039] (e-2) Density The density of the linear low-density polyethylene (E) used in this invention is 0.906 to 0.930 g / cm³. 3 The preferred concentration is 0.908 to 0.929 g / cm³. 3 More preferably, 0.910 to 0.928 g / cm³ 3 The density is 0.906 / cm³. 3 Below this level, heat resistance deteriorates. On the other hand, 0.930 g / cm³ 3 Beyond a certain point, the initial peelability deteriorates. Furthermore, from the viewpoint of heat resistance, it is preferable that the density of linear low-density polyethylene (E) is higher than that of ethylene-propylene copolymer (C). (Density (E) > Density (C)) Here, density is measured in accordance with JIS-K6922-2:1997 Annex (for low-density polyethylene) (measurement temperature 23°C).
[0040] (ii) Polymerization method for linear low-density polyethylene (E) The linear low-density polyethylene (E) used in this invention is linear low-density polyethylene polymerized using a multi-site catalyst. Polymerization using a multi-site catalyst allows for a higher content of low-molecular-weight, high-comonomer components, thereby improving release properties. Linear low-density polyethylene (E) is obtained by polymerization using a transition metal catalyst, and is polymerized under various conditions such as high-pressure methods, gas-phase methods, and solution methods. The Ziegler-Natta catalyst is particularly preferred as the transition metal catalyst.
[0041] (3) Low-density polyethylene (D) produced by high-pressure radical polymerization. The polyethylene resin composition (F) of the present invention preferably further contains high-pressure radical polymerization low-density polyethylene (D) (hereinafter also referred to as low-density polyethylene (D)) having the following characteristics (d-1) to (d-2). High-pressure radical polymerization low-density polyethylene (LDPE) is low-density polyethylene (LDPE) obtained by high-pressure radical polymerization, and is preferably long-chain branched low-density polyethylene. (d-1) MFR (190℃, 21.18N load) is 0.1~20g / 10min (d-2) Density of 0.915~0.930 g / cm³ 3 The polyethylene resin composition (F) contains low-density polyethylene (D) produced by high-pressure radical polymerization, which stabilizes the moldability of the extruded coating.
[0042] (i) Properties of low-density polyethylene (D) produced by high-pressure radical polymerization (d-1)MFR The melt flow rate (MFR: 190°C, 21.18N load) of the high-pressure radical polymerization low-density polyethylene (D) (hereinafter sometimes abbreviated as "low-density polyethylene (D)") used in the present invention is 0.1 to 20 g / 10 min, preferably 0.5 to 15 g / 10 min, and more preferably 1 to 15 g / 10 min. If the MFR is less than 0.1 g / 10 min, the ductility becomes insufficient, and film breakage occurs during high-speed molding. On the other hand, if the MFR exceeds 20 g / 10 min, the molten film becomes unstable. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Annex (190°C, 21.18N load).
[0043] (d-2) Density The density of the low-density polyethylene (D) used in this invention is 0.915 to 0.930 g / cm³. 3 The concentration is preferably 0.916 to 0.926 g / cm³. 3 More preferably, 0.917 to 0.925 g / cm³ 3 Its density is 0.915 g / cm³. 3 Below 0.93 g / cm³, stickiness increases. On the other hand, above 0.93 g / cm³, adhesion becomes poor. Here, density is measured in accordance with JIS-K6922-2:1997 Annex (for low-density polyethylene) (measurement temperature 23°C).
[0044] (ii) Polymerization method for low-density polyethylene (D) by high-pressure radical polymerization The low-density polyethylene (D) used in this invention is generally produced using a tank reactor or a tubular reactor in the presence of a radical generator at a polymerization pressure of 1000 to 3000 kg / cm². 2 This process is carried out by polymerizing ethylene under conditions of polymerization temperature of 150-300°C. The molecular weight-free polymer (MFR) can be adjusted by using hydrocarbons such as hydrogen, methane, and ethane as molecular weight modifiers.
[0045] (4) Composition ratio of ethylene-propylene copolymer (C), linear low-density polyethylene (E), and low-density polyethylene (D) The polyethylene resin composition (F) used in the releaseable resin composition of the present invention contains linear low-density polyethylene (E) polymerized using a multi-site catalyst and contains an ethylene-propylene copolymer (C). In the present invention, when the polyethylene resin composition (F) contains ethylene-propylene copolymer (C), linear low-density polyethylene (E), and high-pressure radical polymerization low-density polyethylene (D), it is preferable that the polyethylene resin composition (F) contains 95 to 10% by weight of ethylene-propylene copolymer (C) and linear low-density polyethylene (E) and 5 to 90% by weight of high-pressure radical polymerization low-density polyethylene (D), and it is even more preferable that it contains 90 to 15% by weight of ethylene-propylene copolymer (C) and linear low-density polyethylene (E) and 10 to 85% by weight of high-pressure radical polymerization low-density polyethylene (D). When the ratio of the total amount of ethylene-propylene copolymer (C) and linear polyethylene (E) to the content of high-pressure radical polymerized low-density polyethylene (D) falls within the above range, a balance can be achieved between release properties and moldability.
[0046] Furthermore, when the polyethylene resin composition (F) used in the present invention contains ethylene-propylene copolymer (C), linear low-density polyethylene (E), and low-density polyethylene (D), the ratio of ethylene-propylene copolymer (C), linear low-density polyethylene (E) to high-pressure radical polymerization low-density polyethylene (D) is preferably (C):(E):(D) 0-80% by weight:5-80% by weight:5-90% by weight, more preferably 0-55% by weight:15-80% by weight:5-70% by weight, and even more preferably 0-30% by weight:30-80% by weight:10-50% by weight. When the proportions of ethylene-propylene copolymer (C), linear polyethylene (E), and high-pressure radical polymerization low-density polyethylene (D) are within the above range, a balance can be achieved between release properties and moldability.
[0047] (4) Properties of polyethylene resin composition (F) In the releaseable resin composition of the present invention, the polyethylene resin composition (F) preferably satisfies the following characteristics (f-1) to (f-2). (f-1) MFR is 1-100g / 10min (f-2) Density of 0.91-0.93 g / cm³ 3
[0048] (f-1)MFR The melt flow rate (MFR: 190°C, 21.18N load) of the polyethylene resin composition (F) used in the present invention is preferably 1 to 100 g / 10 min, more preferably 1 to 80 g / 10 min, and even more preferably 5 to 60 g / 10 min. An MFR of less than 1 g / 10 min is undesirable because it results in poor ductility during molding and increases the motor load in the extruder. On the other hand, an MFR exceeding 100 g / 10 min is undesirable because it makes the state of the molten film unstable during molding. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Annex (190°C, 21.18N load).
[0049] (f-2) Density The density of the polyethylene resin composition (F) used in the present invention is preferably 0.91 to 0.93 g / cm³. 3 More preferably, 0.91 to 0.928 g / cm³ 3 And more preferably 0.91 to 0.926 g / cm³. 3 Its density is 0.91 g / cm³. 3 If the density is less than 0.93 g / cm³, it will result in poor heat resistance, which is undesirable. On the other hand, a density of 0.93 g / cm³ is undesirable. 3 Exceeding this limit is undesirable because it results in poor peelability. Here, density is measured in accordance with JIS-K6922-2:1997 Annex (for low-density polyethylene) (measurement temperature 23°C).
[0050] (5) Other ingredients The polyethylene resin composition (F) used in the present invention or the release resin composition made therefrom may contain additives such as antioxidants commonly used in polyethylene resins, such as phenolic and phosphorus-based agents, stabilizers such as metal soaps, antiblocking agents, lubricants, dispersants, pigments such as organic or inorganic colorants, antifogging agents such as unsaturated fatty acid esters, antistatic agents, ultraviolet absorbers, light stabilizers, and nucleating agents, as needed, provided that the release agent properties are not impaired. For example, a preferred range for the antioxidant is 5000 ppm or less by weight, more preferably 3000 ppm or less, and even more preferably 1000 ppm or less. Furthermore, other thermoplastic resins such as LDPE, C4-LLDPE, HAO-LLDPE, polyethylene-based resins such as ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-acrylic acid ester copolymer (EEA, EMA, EMMA, etc.), and high-density polyethylene (HDPE), adhesive resins such as ethylene-maleic anhydride copolymer, polypropylene-based resins, and polystyrene resins may be blended, provided that the properties of the polyethylene resin composition layer are not impaired. Furthermore, it is preferable that the polyethylene resin composition (F) of the present invention does not contain a crosslinking agent.
[0051] 2. Release film Another embodiment of the present invention is a release film having at least two layers, a resin layer (A) and a base layer (B), wherein the resin layer (A) contains the polyethylene resin composition (F) of the present invention, is formed directly on the base layer (B) or on top of other resin layers laminated on the base layer, and at least one resin layer (A) is the outermost layer (hereinafter also referred to as "the release film of the present invention"). The following describes the layers and other components that make up the release film of the present invention.
[0052] (1) Resin layer (A) The resin layer (A) comprises the polyethylene resin composition (F) of the present invention. Details of the polyethylene resin composition (F) of the present invention are as described in detail in the releaseable resin composition of the present invention. The resin layer (A) is formed either directly on the base layer (B) or by laminating it on top of another resin layer laminated on the base layer. The other resin layer and the method of laminating the resin layer (A) onto the base layer (B) will be described later.
[0053] At least one resin layer (A) is located on the outermost layer of the release film. Here, "the resin layer (A) is located on the outermost layer of the release film" means that the surface of the resin layer (A) is in contact with the adhesive layer. Furthermore, if the release film has two or more resin layers (A), the resin layers (A) other than the outermost layer may be positioned between the multilayer films.
[0054] (2) Base material layer (B) The base material layer (B) used in the present invention is not particularly limited, but a film mainly composed of paper, polyethylene resin, polypropylene resin, polyethylene terephthalate resin, or nylon resin, or a cloth base material made using a stretched yarn base material mainly composed of these materials is preferred. Examples include a single-layer film or a laminated film made of the same or different materials as paper, polypropylene resin, polyethylene terephthalate resin, or nylon resin. Films using polyethylene resin, polyethylene terephthalate resin, or nylon resin are preferably stretched films. If the base material layer (B) contains a resin other than paper, polypropylene resin, polyethylene terephthalate resin, or nylon resin, the resins listed later as examples of other base material layers can be used. The substrate layer may be subjected to printing, vapor deposition, various coatings, etc.
[0055] (3) Composition and manufacturing method of release film The release film of the present invention has at least two layers, a resin layer (A) containing the polyethylene resin composition (F) described above and a base layer (B), wherein the resin layer (A) is formed either directly on the base layer (B) or laminated on another resin layer laminated on the base layer. At least one surface of the base layer (B) is formed by bonding the resin layer (A) containing the polyethylene resin composition (F) either directly or on another resin layer laminated on the base layer. Furthermore, in the release film of the present invention, it is necessary that at least one resin layer (A) containing the polyethylene resin composition (F) be the outermost layer. This enables the release properties to be achieved. Regarding the structure of the release film, if the release film has one resin layer (A), examples of configurations include base layer (B) / resin layer (A) and base layer (B) / other resin layer / resin layer (A). Furthermore, if the release film has two or more resin layers (A), examples of configurations include "resin layer (A) / other resin layer / base layer (B) / resin layer (A)" and "resin layer (A) / other resin layer / base layer (B) / other resin layer / resin layer (A)", but the film is not limited to these.
[0056] Other base material layers include base material layers different from base material layer (B), and examples include plastic films or sheets such as polyamide resins, polyester resins, ethylene-vinyl acetate copolymer saponified products, polyvinylidene chloride, and polycarbonate; stretched products of the above films or sheets; printed materials; secondarily processed films or sheets such as metal vapor-deposited products; metal foils or metal plates such as aluminum, iron, copper, and alloys mainly composed of these materials; cellophane; paper; woven fabrics; nonwoven fabrics; and the like. Furthermore, other resin layers include resin layers different from the release layer (A), and examples include polyethylene-based resins such as LDPE, C4-LLDPE, HAO-LLDPE, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-acrylic acid ester copolymer (EEA, EMA, EMMA, etc.), high-density polyethylene (HDPE), adhesive resins such as ethylene-maleic anhydride copolymer, polypropylene-based resins, polystyrene resins, and other thermoplastic resins.
[0057] The release film of the present invention is manufactured by forming the resin layer (A) directly on a base layer (B) or by laminating it on another resin layer laminated on the base layer. The specific manufacturing method is not particularly limited, but for example, a so-called extrusion coating method is preferred in which a resin layer containing a polyethylene resin composition (F) is melt-extruded and laminated onto the base layer. Furthermore, it is preferable that the above-mentioned extruded coating is laminated in one or more layers by methods such as single layer, sandwich lamination, co-extrusion lamination, or tandem lamination. The resin layer (A) containing the polyethylene resin composition (F) can be used as an adhesive layer and can also be used as a surface sealant.
[0058] Furthermore, there are no particular limitations on the method for ensuring adhesion with the paper substrate layer, but for example, the substrate surface may be treated. Examples of surface treatment methods include corona discharge treatment, ozone treatment, flame treatment, and low-temperature plasma treatment. Another method is to spray ozone onto the molten resin. If a substrate layer other than paper is provided, it is preferable to perform anchor coating treatment as needed.
[0059] The release film of the present invention is formed by a resin layer (A) containing the above-mentioned polyethylene resin composition (F), and is a release film with excellent peelability from adhesive tape.
[0060] The release film of the present invention exhibits excellent peelability from adhesive tapes. Therefore, it can be used as a release film for adhesive sheets, such as surface protection adhesive sheets or dicing adhesive sheets, when processing silicon wafers used in semiconductor integrated circuits (ICs), etc.
[0061] 3. Adhesive tape Another embodiment of the present invention is an adhesive tape having at least three layers: a resin layer (A), a base layer (B), and an adhesive layer (G), wherein the resin layer (A) contains the polyethylene resin composition (F) of the present invention, and the resin layer (A) is formed either directly on the base layer (B) on the side opposite to the side on which the adhesive layer (G) is provided, or by laminating it on other resin layers laminated on the base layer, and at least one resin layer (A) is the outermost layer (hereinafter also referred to as "the adhesive tape of the present invention").
[0062] The resin layer (A) and the base material layer (B) are as described in detail in the release film of the present invention.
[0063] The adhesive layer (G) is composed of an adhesive composition with an adhesive as the main component.
[0064] The type of adhesive is not particularly limited, but various commonly known adhesives such as rubber-based adhesives, acrylic-based adhesives, urethane-based adhesives, silicone-based adhesives, and vinyl-based adhesives can be used. However, the adhesive layer (G) is preferably made of an acrylic-based adhesive because it is highly adhesive and can be used to select a wide range of substrates. Furthermore, any type of adhesive—one-component, two-component, or emulsion—is acceptable (see, for example, "Dictionary of Adhesion and Adhesion" (supervised by Shozaburo Yamaguchi, published by Asakura Shoten, pp. 118-169, 1993)).
[0065] Furthermore, for example, if the adhesive is an acrylic adhesive, it can be composed of polymers or copolymers mainly consisting of a main monomer component that provides tackiness, a comonomer component that provides adhesion and cohesiveness, and a functional group-containing monomer component for crosslinking points and adhesion improvement.
[0066] Examples of the main monomer components include alkyl acrylates such as ethyl acrylate, butyl acrylate, amyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, cyclohexyl acrylate, benzyl acrylate, and methoxyethyl acrylate, as well as alkyl methacrylates such as butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate.
[0067] Examples of comonomer components include methyl acrylate, methyl methacrylate, ethyl methacrylate, vinyl acetate, styrene, and acrylonitrile.
[0068] Examples of functional group-containing monomer components include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, maleic acid, and itaconic acid; hydroxyl group-containing monomers such as 2-hydroxyethyl acrylate, hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, and N-methylolacrylamide; acrylamide; methacrylamide; and glycidyl methacrylate.
[0069] The inclusion of these components improves the adhesive strength and cohesiveness of the adhesive composition. Furthermore, since such acrylic resins typically do not contain unsaturated bonds in their molecules, their stability against light and oxygen can be improved. In addition, by appropriately selecting the type and molecular weight of the monomers, an adhesive composition with the quality and properties required for the application can be obtained.
[0070] Such adhesive compositions may be either cross-linked or non-cross-linked, but the cross-linked type is more preferred. When using the cross-linked type, an adhesive layer with superior cohesive strength can be formed.
[0071] Examples of crosslinking agents used in crosslinked adhesive compositions include epoxy compounds, isocyanate compounds, metal chelate compounds, metal alkoxides, metal salts, amine compounds, hydrazine compounds, and aldehyde compounds.
[0072] Furthermore, the adhesive composition used in the present invention may contain various additives such as plasticizers, tackifiers, and stabilizers, as needed.
[0073] The average thickness of the adhesive layer (G) is not particularly limited, but is preferably 5 to 200 μm, and more preferably 10 to 100 μm.
[0074] The adhesive layer (G) is provided either directly on the base layer (B) or via another resin layer. One method of providing the adhesive layer (G) is to apply an adhesive composition to the base layer (B) or another resin layer.
[0075] Existing methods such as gravure coating, bar coating, spray coating, spin coating, knife coating, roll coating, and die coating can be used to apply the adhesive composition onto the substrate layer (B) or other resin layer.
[0076] Examples of adhesive compositions in this case include solvent-type, emulsion-type, and hot-melt-type adhesives. [Examples]
[0077] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The measurement methods and resins used in the examples and comparative examples are as follows.
[0078] 1.Measurement method (1) Melt flow rate (MFR): The MFR of ethylene-propylene copolymer, linear low-density polyethylene, high-pressure radical polymerization low-density polyethylene, and polyethylene resin compositions was measured in accordance with JIS-K6922-2:1997 Annex (190°C, 21.18N load). (2) Density: The densities of ethylene-propylene copolymer, linear low-density polyethylene, high-pressure radical polymerization low-density polyethylene, and polyethylene resin compositions were measured in accordance with JIS-K6922-2:1997 Annex (23°C, for low-density polyethylene).
[0079] (3) Monomer quantity, number of branches, number of double bonds: <Sample preparation and measurement conditions> 200 mg of the sample was dissolved in 2.4 ml of o-dichlorobenzene / deuterated bromidebenzene = 4 / 1 (volume ratio) and hexamethyldisiloxane, the chemical shift reference substance, in an NMR sample tube with an inner diameter of 10 mmφ. NMR measurements were performed using a Bruker BioSpin AV400M NMR spectrometer equipped with a 10 mmφ cryoprobe. 13 The 1C-NMR measurement conditions were as follows: sample temperature 120°C, pulse angle 90°, pulse interval 20 seconds, and number of integrations 128 times. The measurement was performed using the broadband decoupling method. 1 The 1H-NMR measurement conditions were as follows: sample temperature 120°C, pulse angle 4.5°, pulse interval 2 seconds, and number of integrations 512 times. <Calculation Method> (i) Monomer quantity, number of branches due to comonomers 13 Using the signal intensity of the 1C-NMR spectrum, propylene can be obtained from the following equation. The amounts of hexene and ethylene were determined. C3(mol%)=I(P)×100 / [I(P)+I(H)+I(E)] C6(mol%)=I(H)×100 / [I(P)+I(H)+I(E)] C2(mol%)=I(E)×100 / [I(P)+I(H)+I(E)] Here, I(P), I(H), and I(H) are quantities represented by the following equations, respectively. I(P) = 0.5 × (I 37.69~37.20 +I 37.90~37.69 +I 37.97~37.90 +I 43.90~42.68 )+I 46.60~45.39 I(H) = 0.5 × (I 34.56~34.22 +I 34.94~34.86 +I 43.60~42.68 ) + 0.5 × (I 34.86~34.70 -I 35.80~35.68 )+I 40.10~39.96 +I 40.80~40.70 I(E) = {0.5 × (I 34.94~34.86 +I 37.90~37.69 I 37.97~37.90 +I 34.56~34.22 +I 37.69~37.20 ) + 0.5 × (I 34.86~34.70 -I 35.80~35.68 )+I 24.90~24.70 +I 24.70~24.52 +I 24.52~24.32 +I 27.28~26.83 +I 27.50~27.28 +I 31.50~28.50 -I(H)} / 2 I represents the integral intensity, and the numerical subscript to I indicates the range of the chemical shift. For example, I 37.69~37.20 This shows the integrated intensity of the 13C signal detected between 37.69 ppm and 37.20 ppm. The chemical shift was set to 1.98 ppm for the 13C signal of hexamethyldisiloxane, and the chemical shifts of other 13C signals were referenced to this value. Furthermore, the number of branches per 1000 carbon atoms in the main chain and side chains was calculated using the following formula. Number of methyl branching molecules (molecules / total 1000C) =C3(mol%)×1000 / {C3(mol%)×3+C6(mol%)×6+ C2 (mol%) × 2 Butyl branching count (number of branches / total 1000C) =C6(mol%)×1000 / {C3(mol%)×3+C6(mol%)×6+ C2 (mol%) × 2
[0080] (ii) Number of double bonds The number of unsaturated bonds per 1000 carbon atoms in the main chain and side chains combined 1 The signal intensity of the H-NMR spectrum was used to determine the following equation. Number of vinylidene particles (particles / total 1000C) = Ivd × 1000 / Itotal Number of vinyl units (units / total 1000C) = Ivi × 1000 / Itotal Number of trisubstituted olefins (units / total 1000C) = Itri × 1000 / Itototal Number of vinylene particles (particles / total 1000C) = Ivnl × 1000 / Itotal I represents the integrated intensity, and the subscript number of I indicates the range of the chemical shift. Here, Ivd 、 Ivi, Itri, Ivnl, and Itotal are quantities represented by the following formulas, respectively. Ivd=(I 4.88~4.44 ) / 2 Ivni=( I 5.52~5.30 ) / 2 Ivi=( I 5.05~4.88 +I 5.85~5.70 ) / 3 Itri=I 5.30~5.05 Itotal=( 0.00~5.85 ) / 2 However, for example, I 5.52~5.30 This shows the integrated intensity of the proton signal detected between 5.52 ppm and 5.30 ppm. The chemical shift was set with the proton signal of hexamethyldisiloxane at 0.09 ppm, and the chemical shifts of signals from other protons were based on this value.
[0081] (4) Melt film stability: The stability of the molten film was visually observed using an extruder with a diameter of 90 mm, a T-die width of 560 mm, a lip width of 0.8 mm, an air gap of 115 mm, a molding temperature of 300°C, and a take-up speed of 100 m / min. A "○" was used when the molten film was stable and could be processed, and a "×" was used when the molten film was unstable and could not be processed to a uniform thickness.
[0082] (5) Measurement of initial peeling force Using a 90Φ extruder laminator, a polyethylene resin composition (F) was extruded onto a substrate under the same conditions as the melt film stability test, with a thickness of 20 μm, to obtain a laminate containing the substrate and polyethylene resin composition (F). This laminate was attached to an acrylic plate 25 mm wide and 300 mm long, with the substrate side facing outwards. In accordance with JIS-Z0237-2009, "Airtight Waterproof Tape KM-30" manufactured by Diatex Co., Ltd. was applied to the polyethylene resin composition (F) of the laminate. After curing overnight (23°C, 50%), the tape peel strength was measured at 180° peel. A maximum peel strength of 5 N or less was marked with ◎. A maximum peel strength of 10 N or less was marked with △. A maximum peel strength exceeding 10 N was marked with ×.
[0083] (6) Measurement of heat-resistant peel strength Similarly, using a laminator in a 90Φ extruder, the polyethylene resin composition (F) was extruded onto the substrate under the same conditions as the melt film stability test, with a thickness of 20 μm, to obtain a laminate containing the substrate and the polyethylene resin composition (F). This laminate was attached to an acrylic plate 25 mm wide and 300 mm long, with the substrate side facing outwards. Following JIS-Z0237-2009, Diatex Co., Ltd.'s "Airtight Waterproof Tape KM-30" was applied to the polyethylene resin composition (F) of the laminate. After 30 days of moist heat aging at 60°C and 90% humidity, followed by one night of curing (23°C and 50% humidity), the tape peel strength at 180° peel was measured. A maximum peel strength change of 10% or less was considered a success.
[0084] 2. Resin materials (1) Ethylene-propylene copolymer (C) C-1: Manufacturing method using ethylene-propylene copolymer (C) produced by the following method (MFR20, density 0.887) (C-1) (i) Preparation of catalyst A catalyst solution was prepared by adding an equimolar amount of "N,N-dimethylaniliniumtetrakis(pentafluorophenyl)borate" to 0.05 moles of the complex "rac-dimethylsilylenebisindenylhafniumdimethyl," which was prepared by the method described in Japanese Patent Publication No. 10-218921, and diluting it with toluene to 50 liters. (ii) Polymerization method A 5.0-liter internal volume agitated autoclave-type continuous reactor was used, and the reactor pressure was maintained at 80 MPa. The raw material gas was continuously supplied at a rate of 40 kg / hour, with the ethylene, propylene, and 1-hexene adjusted as needed. In addition, the catalyst solution described in section (i) "Preparation of Catalyst" above was continuously supplied, and the polymerization temperature was adjusted as needed within the range of 150 to 250°C to obtain an ethylene-α-olefin copolymer. The physical properties of the obtained ethylene-propylene copolymer (C-1) are shown in Tables 1 and 2.
[0085] [Table 1]
[0086] (2) Linear low-density polyethylene (E) E-1: Linear polyethylene copolymerized with 1-butene by gas phase using a Ziegler-Natta catalyst (MFR16, density 0.921) E-2: Linear polyethylene copolymerized with 1-butene by gas phase using a Ziegler-Natta catalyst (MFR14, density 0.925) E-3: Linear polyethylene copolymerized with 1-butene by gas phase using a Ziegler-Natta catalyst (MFR2, density 0.915) E'-1: Linear polyethylene copolymerized with 1-hexene by gas phase using a Ziegler-Natta catalyst (MFR2, density 0.920) E'-2: Linear polyethylene copolymerized with 1-butene by gas phase using a Ziegler-Natta catalyst (MFR5, density 0.935) E'-3: Linear polyethylene copolymerized with 1-hexene using a metallocene catalyst (MFR 10.2, density 0.927) E'-4: Linear polyethylene (MFR17, density 0.966) slurry polymerized using Ziegler-Natta catalyst.
[0087] (3) Low-density polyethylene by high-pressure radical polymerization Low-density polyethylene produced by high-pressure radical polymerization, having the physical properties shown in Table 2, was used (D-1 (MFR4, density 0.918)), (D-2 (MFR7, density 0.918)), and (D-3 (MFR8, density 0.919)).
[0088] (Example 1) As the ethylene-propylene copolymer (C), 20% by weight of ethylene-propylene copolymer (C-1) with an MFR of 20 and a density of 0.887 is used, and as the linear low-density polyethylene (E), with an MFR of 16 g / 10 min and a density of 0.921 g / cm³ is used. 3 Linear low-density polyethylene (E-1) 60% by weight, high-pressure low-density polyethylene (D), with an MFR of 4 g / 10 min and a density of 0.918 g / cm³ 3 A polyethylene resin composition (F) consisting of 20% by weight of long-chain branched low-density polyethylene (D-1) produced by high-pressure radical polymerization was granulated using a 40 mm single-screw extruder to obtain polyethylene-based composition pellets. Using the pellets obtained above, in order to evaluate (4) melt film stability, (5) initial peel strength, and (6) heat-resistant peel strength, 50 g / m² of kraft substrate was fed from the feed machine into the laminator of a 90Φ extruder. 2 The material is fed out and used as the base material, and the paper base material surface is subjected to corona treatment at 30W·min / m 2 This paper substrate was treated with Novatec LC600A manufactured by Nippon Polyethylene, and then ozone-treated at 1.5 Nm. 3 / h-16g / m 3 Extrusion lamination was performed under conditions of a take-up speed of 100 m / min and a thickness of 15 μm with the material under control. Furthermore, polyethylene resin composition (F) was laminated to the LC600A layer under conditions of a take-up speed of 100 m / min and a thickness of 20 μm to obtain a laminate (release film) consisting of a kraft layer, an LC600A layer, and a resin layer (A) containing polyethylene resin composition (F), and each was evaluated. The evaluation results of the laminate are shown in Table 2.
[0089] (Example 2) As linear low-density polyethylene (E), it has an MFR of 14 g / 10 min and a density of 0.925 g / cm³. 3Pellets were prepared and evaluated in the same manner as in Example 1, except that a polyethylene resin composition (F) consisting of 65% by weight of linear low-density polyethylene (E-2) and 15% by weight of (D-1) as high-pressure low-density polyethylene (D) was used. The evaluation results are shown in Table 2.
[0090] (Example 3) As linear low-density polyethylene (E), it has an MFR of 2 g / 10 min and a density of 0.915 g / cm³. 3 Pellets were prepared and evaluated in the same manner as in Example 1, except that a polyethylene resin composition (F) consisting of 40% by weight of linear low-density polyethylene (E-3) and 40% by weight of (D-2) as high-pressure low-density polyethylene (D) was used. The evaluation results are shown in Table 2.
[0091] (Comparative Example 1) Pellets were prepared and evaluated in the same manner as in Example 1, except that a polyethylene resin composition (F) was used, consisting of 20% by weight of (C-1) as the ethylene-propylene copolymer (C), 0% by weight of (E-1) as the linear polyethylene (E), and 80% by weight of high-pressure radical polymerization long-chain branched low-density polyethylene (D-3) with an MFR of 8 and a density of 0.919 as the high-pressure low-density polyethylene (D). The evaluation results are shown in Table 2.
[0092] (Comparative Example 2) Pellets were prepared and evaluated in the same manner as in Example 1, except that a polyethylene resin composition (F) was used, consisting of 30% by weight of (C-1) as the ethylene-propylene copolymer (C), 50% by weight of linear polyethylene (E'-4) with an MFR of 17 and a density of 0.966 (high-density polyethylene), and 20% by weight of (D-1) as the high-pressure low-density polyethylene (D). The evaluation results are shown in Table 2.
[0093] (Comparative Example 3) Pellets were prepared and evaluated in the same manner as in Example 1, except that a polyethylene resin composition (F) consisting of (C-1) as the ethylene-propylene copolymer (C), (E'-1) as the linear polyethylene (E), and (D-2) as the high-pressure low-density polyethylene (D) was used. The evaluation results are shown in Table 2.
[0094] (Reference example 1) In Example 2, instead of using linear low-density polyethylene (E-2), a material with an MFR of 5 g / 10 min and a density of 0.935 g / cm³ was used. 3 Except for using linear polyethylene (E'-2), pellets were prepared and evaluated in the same manner as in Example 2. The evaluation results are shown in Table 2.
[0095] (Reference example 2) In Example 2, instead of using linear low-density polyethylene (E-2), a material with an MFR of 10.2 g / 10 min and a density of 0.927 g / cm³ was used. 3 Except for using metallocene-based linear low-density polyethylene (E'-3), pellets were prepared and evaluated in the same manner as in Example 2. The evaluation results are shown in Table 2.
[0096] [Table 2]
[0097] For Examples 1 and 2, Comparative Example 1, and Reference Example 1 obtained in Table 2, the relationship between the peel strength and the time of the wet heat aging test is shown as a graph in Figure 3. In the graph, the X-axis (horizontal axis) represents the number of days of moist heat aging, and the Y-axis (vertical axis) represents the tape peel strength. A smaller value on the Y-axis is preferable. As is clear from the results in Table 2 and Figure 3, the release resin composition according to the embodiment of the present invention and the release film obtained thereby exhibit excellent melt film stability, excellent initial release strength, and good release strength after moist heat aging. Here, Reference Examples 1 and 2 are results obtained using release compositions related to the inventors' related applications, and while the initial release force is at a level that is not problematic for practical purposes, the release resin composition according to the examples of the present invention has an even more improved initial release force than these reference examples by containing a specific linear low-density polyethylene (E) as defined in the present invention. On the other hand, when the linear low-density polyethylene resin (E) is not included (Comparative Examples 1 and 2), the initial peel strength is high, which is undesirable. Also, when the density of the linear polyethylene resin is higher than the specified range of the present invention (Comparative Example 2), the initial peel strength is high, which is undesirable. Furthermore, when 1-hexene is used as the comonomer (Comparative Example 3), the initial peel strength is also high, which is undesirable. [Industrial applicability]
[0098] Laminates using the release resin composition of the present invention as the release layer can be used as release films, release sheets, etc., where easy peeling is required.
Claims
1. A releaseable resin composition comprising a polyethylene resin composition (F) characterized by containing an ethylene-propylene copolymer (C) having all of the following properties (c-1) to (c-5), and linear low-density polyethylene (E) polymerized using a multi-site catalyst having the following properties (e-1) to (e-2). (c-1) A compound containing 80 to 98 mol% of constituent units derived from ethylene as the main component, 2 to 20 mol% of constituent units derived from propylene as an essential minor component, and 7 mol% or less of constituent units derived from a third α-olefin other than ethylene and propylene as an optional minor component. (However, if the material contains constituent units derived from the third α-olefin, the sum of constituent units derived from ethylene, propylene, and the third α-olefin shall not exceed 100 mol%.) (c-2) MFR (190°C, 21.18N load) is 1-100g / 10min (c-3) Density of 0.88–0.94 g / cm³ 3 (c-4) The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.20 (particles / total 1000C) or more. (However, the number of vinyl and vinylidene atoms is the number per 1000 carbon atoms in the main chain and side chains combined, as measured by NMR.) (c-5) The number of branches (Y) and density (X) of comonomers in an ethylene-propylene copolymer satisfy the following relationship (1). Equation (1): (Y) ≥ -566 × (X) + 540 (However, Y is the number of carbon atoms per 1000 total carbon atoms in the main chain and side chains as measured by NMR.) (e-1) MFR (190°C, 21.18N load) is 0.1 to 30 g / 10 min (e-2) Density of 0.906–0.930 g / cm³ 3
2. The releaseable resin composition according to claim 1, characterized in that the polyethylene resin composition (F) further contains high-pressure radical polymerization low-density polyethylene (D) having the following properties (d-1) to (d-2). (d-1) MFR (190°C, 21.18N load) is 0.1-20g / 10min (d-2) Density of 0.915–0.930 g / cm³ 3
3. The releaseable resin composition according to claim 2, characterized in that the polyethylene resin composition (F) contains 95 to 10% by weight of ethylene-propylene copolymer (C) and linear low-density polyethylene (E) and 5 to 90% by weight of low-density polyethylene (D) produced by high-pressure radical polymerization.
4. The releaseable resin composition according to any one of claims 1 to 3, characterized in that the polyethylene resin composition (F) further satisfies the following characteristics (f-1) to (f-2). (f-1) MFR is 1-100g / 10 min (f-2) Density of 0.91–0.93 g / cm³ 3
5. The releaseable resin composition according to any one of claims 1 to 3, characterized in that the ethylene-propylene copolymer (C) further satisfies the following physical property (c-4'). (c-4') The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.35 (particles / total 1000C) or more. (However, the number of vinyl and vinylidene atoms is the number per 1000 carbon atoms in the main chain and side chains combined, as measured by NMR.)
6. The releaseable resin composition according to any one of claims 1 to 3, characterized in that the ethylene-propylene copolymer (C) further satisfies the following physical properties (c-5'). (c-5') The number of branches (Y) and density (X) of comonomers in an ethylene-propylene copolymer satisfy the relationship shown in equation (2) below. Equation (2): (Y) ≥ -1360 × (X) + 1270 (However, Y is the number of carbon atoms per 1000 total carbon atoms in the main chain and side chains as measured by NMR.)
7. The release resin composition according to any one of claims 1 to 3, characterized in that the ethylene-propylene copolymer (C) substantially does not contain any constituent units derived from a third α-olefin other than ethylene and propylene.
8. A release film having at least two layers, a resin layer (A) and a base layer (B), wherein the resin layer (A) contains the polyethylene resin composition (F) described in any one of claims 1 to 3, and is formed by laminating it directly on the base layer (B) or on other resin layers laminated on the base layer, and at least one resin layer (A) is the outermost layer.
9. The release film according to claim 8, characterized in that the resin layer (A) is formed on the base material layer (B) by an extrusion coating method.
10. An adhesive tape having at least three layers: a resin layer (A), a base layer (B), and an adhesive layer (G), wherein the resin layer (A) comprises the polyethylene resin composition (F) described in any one of claims 1 to 3, and the resin layer (A) is formed either directly on the base layer (B) on the side opposite to the side on which the adhesive layer (G) is provided, or by laminating it on other resin layers laminated on the base layer, and at least one resin layer (A) is the outermost layer.
11. The adhesive tape according to claim 10, characterized in that the adhesive layer is made of an acrylic adhesive.
Citation Information
Patent Citations
release film without silicone
JP1999508958A
Releasing liner and adhesive sheet
JP2000119411A
Release liner and pressure-sensitive adhesive sheet
JP2000239624A